JOSEPH SCHACHT, TEORI SKEPTISISME HADIS DAN BANTAHAN-BANTAHANNYA - Nurlaila Indah; M. Albi Albana; Umi Sumbulah (Diya Al-Afkar: Jurnal Studi al-Quran dan al-Hadis, 2021)
This paper examines how the views of Joseph Schacht is an orientalist scholar in the field of Islamic law who has done a lot of hadith criticism. Through his work, The Origins of Muhammadan Jurisprudence, Schacht states that the hadiths were made by scholars of the second and third centuries of hijra because in the past the hadiths had not been well codified. The view of this student of Ignaz Goldziher towards the hadith was developed by three theories, namely, the projecting back theory, the theory of argumentum e silentio, and the common link theory.